Structure and Function of Systemic Arteries: Reflections on the Arterial Pulse. (16th July 2018) - O'Rourke, Michael F; Adji, Audrey; Safar, Michel E
Abstract: "Structure and Function of Arteries"—is a topic of great importance to those who deal with arterial hypertension, since it links the source of flow, the left ventricle of the heart (whose output is pulsatile) to the peripheral tissues (whose flow is near continuous). The arterial tree acts passively as a conduit and cushion, and the interaction of heart, arterial tree, and organs is conventionally gauged on the basis of blood pressure measured by cuff in a conveniently located place (the brachial artery). For any precision and perspective to be gained, measurements of brachial systolic and diastolic pressure need be supplemented by other information. When such information is gained, one can understand how beautifully the arterial tree is tuned to the beat of the heart in animals of different size and shape and in humans at age 30 through the first third of a 3 billion beat lifetime. After age 30, the beats themselves progressively destroy the human arteries and their tuning to the heart, with emergence of clinical syndromes. In this review, the subject is tackled quantitatively on the basis of published numerical, physical, physiological, and pathophysiological basis, with principal focus on the beat of the heart, the pulse of the arteries, and their interaction.